2013
DOI: 10.1152/ajpendo.00039.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for ovulation induction in polycystic ovary syndrome: a randomized controlled trial

Abstract: Acupuncture has been demonstrated to improve menstrual frequency and to decrease circulating testosterone in women with polycystic ovary syndrome (PCOS). Our aim was to investigate whether acupuncture affects ovulation frequency and to understand the underlying mechanisms of any such effect by analyzing LH and sex steroid secretion in women with PCOS. This prospective, randomized, controlled clinical trial was conducted between June 2009 and September 2010. Thirty-two women with PCOS were randomized to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 48 publications
9
100
0
Order By: Relevance
“…Before this study, 2 trials demonstrated that acupuncture was effective for ovulation induction compared with no treatment or regularly meeting with a therapist. 13,14 The only shamcontrolled trial using a nonpenetrating sham was underpowered for investigating live births, 8 but it found ovulation rates between active and control acupuncture similar to those observed in this study. That study used the nonpenetrating Streitberger placebo needle, 28 whereas superficial needle placement was used as a control in this study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Before this study, 2 trials demonstrated that acupuncture was effective for ovulation induction compared with no treatment or regularly meeting with a therapist. 13,14 The only shamcontrolled trial using a nonpenetrating sham was underpowered for investigating live births, 8 but it found ovulation rates between active and control acupuncture similar to those observed in this study. That study used the nonpenetrating Streitberger placebo needle, 28 whereas superficial needle placement was used as a control in this study.…”
Section: Discussionsupporting
confidence: 68%
“…29 The ovulation rates in the active and control acupuncture groups in this trial were higher than rates in trials with a no-intervention control group. 13,14 Thus, the acupuncture procedure, unrelated to needle placement or stimulation, may have placebo effects. There was no statistically significant difference between active and control acupuncture in clinical or biochemical variables or serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The vital acupoints include Guanyuan (CV 4), Zhongwan (CV 12), Tianshu (ST 25), Zusanli (ST 36), and Sanyinjiao (SP 6). In addition, acupoints in other meridians, such as Zigong (EX-CA1) and Taichong (LR 3), are also commonly used in clinical practice (Cui et al, 2011;Johansson et al, 2013;Lei and Feng, 2014).…”
Section: Application Of Ea/teas In Treating Pcosmentioning
confidence: 99%
“…Acupuncture has been used in treating gynecological and reproductive disorders for thousands of years (Zhou and Qu, 2009). Electroacupuncture (EA) and transcutaneous electrical acupoint stimulation (TEAS), the modern therapies derived from traditional acupuncture, have received increasing attention in recent years (Han and Ho, 2011;Johansson et al, 2013). The present group consensus is intended to provide guidelines for physicians and practitioners using EA or TEAS in the treatment of reproductive disorders (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have indicated that acupuncture improves ovulatory dysfunction and insulin sensitivity, and decreases testosterone, in patients with PCOS. [8][9][10] Given that women with PCOS undergoing ovarian stimulation are considered to be at increased risk for OHSS, it is important to confirm the effects and safety of acupuncture as an adjunct treatment in this particular population, to maximise the success rates of IVF or ICSI.…”
Section: Introductionmentioning
confidence: 99%